2017
DOI: 10.1159/000468546
|View full text |Cite
|
Sign up to set email alerts
|

Antacid Therapy and Disease Progression in Patients with Idiopathic Pulmonary Fibrosis Who Received Pirfenidone

Abstract: Background: Gastroesophageal reflux disease is a potential risk factor for idiopathic pulmonary fibrosis (IPF) progression; however, the impact of antacid therapy (AAT) is under debate. Objective: To evaluate the effect of AAT on IPF progression in pirfenidone-treated patients. Methods: This post hoc analysis included patients with IPF who received pirfenidone in 3 trials (CAPACITY [PIPF-004/PIPF-006] and ASCEND [PIPF-016]). Pulmonary function, exercise tolerance, survival, hospitalizations, and adverse events… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
74
0
7

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 66 publications
(83 citation statements)
references
References 34 publications
2
74
0
7
Order By: Relevance
“…There are no currently proven beneficial management strategies for patients with AE-IPF [1][2][3][4]8], but there are several possible approaches that may influence prognosis [8,71,72].…”
Section: Influence Of Management Strategiesmentioning
confidence: 99%
See 1 more Smart Citation
“…There are no currently proven beneficial management strategies for patients with AE-IPF [1][2][3][4]8], but there are several possible approaches that may influence prognosis [8,71,72].…”
Section: Influence Of Management Strategiesmentioning
confidence: 99%
“…However, a recent study reported that antacid therapy increased the risk of overall infection and pulmonary infection in patients with advanced IPF (i.e. FVC<70%) [72]. Therefore, the balance of benefit and risk of antacid therapy for prevention of AE-IPF may vary by clinical situation.…”
Section: Preventive Measuresmentioning
confidence: 99%
“…Post hoc and retrospective data that reported on positive effects of antacid therapies with regard to lung function decline and acute exacerbations [88,89] have led to a conditional recommendation for the use of antacid drugs in all IPF patients [3]. However, more recent data could not support these findings and even hypothesised a higher pulmonary infection rate in patients taking antacid drugs [90][91][92]. Therefore, future research must aim to prospectively assess the impact of comorbidities on symptoms and outcome as well as respective treatment measures.…”
Section: Treatment Of Comorbiditiesmentioning
confidence: 99%
“…A prospectively designed, pre-specified analysis of the placebo arms of the IPFnet trials using well designed case-report forms to proactively capture data regarding GORD and therapeutic intervention, revealed that the use of AAT for any reason was associated with fewer exacerbations and significantly less worsening of forced vital capacity than in patients without AAT during the study period, but without effects on all-cause mortality [10]. However, post hoc and exploratory analyses from the two groups from three clinical trials on pirfenidone in IPF did not reveal differences in the rate of decrease of lung function or mortality when comparing AAT users versus non-users at baseline [11,12]. Several questions regarding the association of GORD and IPF and management of GORD in patients with IPF need to be addressed in much needed prospective studies [6].…”
mentioning
confidence: 98%
“…Comparing pooled hazard ratios from studies affected by immortal time bias (0.46, 95% CI 0.30-0.69) with those which avoided this effect (0.94; 95% CI 0.76-1.17) one may assume that the direction of this effect could still tend towards a protective effect. While this may, in part, be explained by association with improved survival in patients with IPF allegedly suffering from GORD regardless of treatment [1,9], the retrospective studies do not provide the much-needed answer to the question about the apparent beneficial or adverse effects of AAT [11,12]. Several confounding factors in the observational studies that introduce risk of bias (e.g.…”
mentioning
confidence: 99%